2013
DOI: 10.1021/la304264g
|View full text |Cite
|
Sign up to set email alerts
|

Multimode Multidrop Serial Coalescence Effects during Condensation on Hierarchical Superhydrophobic Surfaces

Abstract: The prospect of enhancing the condensation rate by decreasing the maximum drop departure diameter significantly below the capillary length through spontaneous drop motion has generated significant interest in condensation on superhydrophobic surfaces (SHS). The mobile coalescence leading to spontaneous drop motion was initially reported to occur only on hierarchical SHS, consisting of both nanoscale and microscale topological features. However, subsequent studies have shown that mobile coalescence also occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
196
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 207 publications
(206 citation statements)
references
References 72 publications
4
196
3
3
Order By: Relevance
“…In principle, any sub-microscale structures with a small feature size (tip size and interspace) and a certain height (or depth) can become effective candidates for creating CMDSP surfaces. In fact, except for arrays of closely packed nanotips, including nanocones, [22,27,50,69,70] nanoneedles, [21,28,31,66,71] nanopencils, [23] and tip-like nanotubes, [72,73] other architectures such as nano wires, [24,74] nanosheet arrays, [20,29,62,75] nanorod-capped nano pores, [68,76] the porous structure of nanoparticles, [67] nanoparticle aggregates, [73,[77][78][79][80] and two-tier structures [25,57,63,[81][82][83][84][85][86][87][88][89] have all been verified to be effective in endowing material surfaces with the desired CMDSP functionality as long as they follow these basic construction rules.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…In principle, any sub-microscale structures with a small feature size (tip size and interspace) and a certain height (or depth) can become effective candidates for creating CMDSP surfaces. In fact, except for arrays of closely packed nanotips, including nanocones, [22,27,50,69,70] nanoneedles, [21,28,31,66,71] nanopencils, [23] and tip-like nanotubes, [72,73] other architectures such as nano wires, [24,74] nanosheet arrays, [20,29,62,75] nanorod-capped nano pores, [68,76] the porous structure of nanoparticles, [67] nanoparticle aggregates, [73,[77][78][79][80] and two-tier structures [25,57,63,[81][82][83][84][85][86][87][88][89] have all been verified to be effective in endowing material surfaces with the desired CMDSP functionality as long as they follow these basic construction rules.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%
“…Benefiting from the wellestablished top-down micro-and nanofabrication technologies, various silicon nanostructures (e.g., nanoneedles [71,90] and nanocones [69] ) and their combination with regular microstructures (e.g., micropillars [25,85] and micropyramids [84] ) have been successively made for creating bionic CMDSP surfaces, and the transport behaviors of condensate microdrops at the microscale showing the typical coalescence-induced self-propelling details of condensed microdrops on the nanoneedle surface. f,g) Reproduced with permission.…”
Section: Metal-based Cmdsp Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Previous studies [14,15] have shown that on superhydrophobic surfaces with only microscale roughness, condensate droplets tend to nucleate and grow in the cavities between microstructures, forming sticky droplets in the Wenzel state, [16] which are pinned strongly to the surface at the three-phase contact line. To overcome this limitation, superhydrophobic surfaces with nanoscale [17,18] or hybrid micro/nanoscale [19][20][21][22][23][24] roughness have been developed that enable the formation of condensate droplets in the Cassie state.…”
mentioning
confidence: 99%
“…[18][19][20][21][22][23] These studies are limited to silicon substrates, however, and are not suitable for scaled-up industrial applications. Therefore, it is highly desirable to develop hybrid surfaces that are compatible with materials commonly employed for heat transfer applications, such as copper.…”
mentioning
confidence: 99%